Finite-element Simulation of Kevlar Yarns and Fabrics in Assessing its Mechanical Protective Performance under Projectile Impact Loading (Journal of Fiber Bioengineering and Informatics, 2018)
With the increasing concern on occupational safety, people pay more and more attention to mechanical protection. At present, the focus of relevant researches is on the mechanical protection performance of high-performance fibres and high-strength fabrics. The influences that mechanical properties of fabrics have on the mechanical protective performance of clothing are discussed in this paper. Woven fabrics made of high-performance fibres have been widely used as mechanical protective clothing in the form of flexible armour such as bullet-proof vests, stab-resistant garments and so on. The mechanical response and energy absorption characteristics of fabrics under high-speed projectile impact are dependent upon intrinsic constitutive relations, construction parameters such as fabric type, fabric construction, areal density, projectile shape, and impact conditions such as impact velocity and boundary conditions.This project involves the study of Kevlar fibre which is a poly-p-phenylene terephthamide (PPTA) fibre. The Kevlar fabric studied in this paper is plain woven. Experiments about construction parameters of Kevlar yarns are proposed to obtain the mechanical properties of woven fabrics. This paper also investigates the finite-element simulation of huge impact on Kevlar fabric by proposing a material model, which incorporates stretch and elasticity restoring property and failure criteria. A non-linear, explicit, three-dimensional finite-element program ANSYS is used to simulate the response of fabric to high-speed projectile impact with two Hookean springs and a Newtonian dashpot.
Keywords: Finite-element modeling; mechanical protective clothing; ballistic impact; energy absorption